Plansarts - Ramos, Marco (Tufts Archival Research Center, 2025)
Acrylic on canvas panel. Art created as part of Project PAINT, in association with the Richard J. Donovan Correctional Facility in San Diego, and California State Prison- Centinela in Imperial, California.